OGLE-2019-BLG-0825: constraints on the source system and effect on binary-lens parameters arising from a five-day xallarap effect in a candidate planetary microlensing event - Satoh, Yuki K.; Koshimoto, Naoki; Bennett, David P.; Sumi, Takahiro; Rattenbury, Nicholas James; Suzuki, Daisuke; Miyazaki, Shota; Bond, Ian A.; Udalski, Andrzej; Gould, Andrew; Bozza, Valerio; Dominik, Martin; et al. (The astronomical journal, 2023)
We present an analysis of microlensing event OGLE-2019-BLG-0825. This event was identified as a planetary candidate by preliminary modeling. We find that significant residuals from the best-fit static binary-lens model exist and a xallarap effect can fit the residuals very well and significantly improves χ 2 values. On the other hand, by including the xallarap effect in our models, we find that binary-lens parameters such as mass ratio, q, and separation, s, cannot be constrained well. However, we also find that the parameters for the source system such as the orbital period and semimajor axis are consistent between all the models we analyzed. We therefore constrain the properties of the source system better than the properties of the lens system. The source system comprises a G-type main-sequence star orbited by a brown dwarf with a period of P ∼ 5 days. This analysis is the first to demonstrate that the xallarap effect does affect binary-lens parameters in planetary events. It would not be common for the presence or absence of the xallarap effect to affect lens parameters in events with long orbital periods of the source system or events with transits to caustics, but in other cases, such as this event, the xallarap effect can affect binary-lens parameters.
Gesehen am 04.01.2024
The MOA Collaboration: Fumio Abe, Richard Barry, Aparna Bhattacharya [und 19 weitere Verfasser] ; The OGLE Collaboration: Przemek Mróz, Radosław Poleski , Jan Skowron [und 10 weitere Verfasser] ; The KMTNet Collaboration: Michael D. Albrow, Sun-Ju Chung, Cheongho Han [und 18 weitere Verfasser] ; The MiNDSTEp Collaboration: Uffe G. Jørgensen, Penélope Longa-Peña, Markus Hundertmark [und 14 weitere Verfasser]